Method for dehydrating and shaping waterlogged wooden cultural relics

By applying protective material solution or suspension step by step, the problem of difficulty in penetration of protective materials in saturated wood cultural relics is solved, effective reinforcement and dehydration and shaping are achieved, the protection effect is improved and irreversible shrinkage and deformation are reduced.

CN119748588AActive Publication Date: 2025-04-04SHANGHAI UNIV OF MEDICINE & HEALTH SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510054064.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively promote the penetration of protective materials in saturated wood cultural relics, resulting in poor reinforcement and protection effect, and irreversible shrinkage and deformation are prone to occur during dehydration and shaping.

Method used

By applying a protective material solution or suspension step by step, drying with a constant temperature and humidity environment, it promotes the diffusion and adsorption of protective materials in the shallow wood structure, achieves local support and reinforcement, and controls dehydration to avoid structural collapse.

Benefits of technology

It effectively promotes the penetration of protective materials in saturated wood cultural relics, improves the reinforcement effect, reduces the volume shrinkage rate, and achieves rapid and safe dehydration and shaping.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119748588A_ABST
    Figure CN119748588A_ABST
Patent Text Reader

Abstract

The invention provides a method for dehydrating and shaping a waterlogged wooden cultural relic. The method comprises the following steps: preparing a protective material solution or suspension; carrying out drying treatment on the water-saturated wooden cultural relics in an environment with constant temperature and humidity; a protective material solution or suspension is applied to the water-saturated wooden cultural relic, and then drying is carried out; repeating the steps for multiple times, increasing the dewatering time and the protective material applying time when the weight increment of the protective material is not changed, and performing a new cycle; then drying the treated water-saturated wooden cultural relics in a constant-temperature and constant-humidity environment; and then transferring to a room temperature condition and drying to constant weight. According to the method, the permeation amount of the protective material can be effectively increased, and the volume shrinkage rate of the protected wood is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wood processing, and relates to a method for processing water-saturated wooden cultural relics, in particular to a method for dehydrating and shaping water-saturated wooden cultural relics. Background Art

[0002] Water-saturated wooden cultural relics have been underwater or in flooded soil for a long time, and their water-soluble polysaccharides have been leached, and cellulose and hemicellulose have been decomposed by anaerobic fungi. In a water-saturated and oxygen-deficient environment, since the microorganisms that can degrade lignin are aerobic, the main component left in water-saturated wooden cultural relics is lignin. Water-saturated wooden cultural relics mainly rely on residual lignin and absorbed water to maintain their shape, and are porous, soft and brittle. Once water-saturated wood is exposed to the air, the free water and bound water from the surface to the inside of the water-saturated wood gradually evaporate, and the resulting surface tension causes the fragile cell walls to collapse, causing irreversible shrinkage and deformation of the entire wood. The reinforcement and protection of water-saturated wooden cultural relics, which are both fragile and have poor permeability, has become a challenging problem in the field of cultural relic protection.

[0003] The dehydration and shaping of water-saturated wooden cultural relics can be divided into physical treatment methods and chemical treatment methods. Physical methods such as natural drying, freeze drying, and supercritical drying have dehydration effects but no reinforcement effects, and are not suitable for severely decayed and large-scale wooden cultural relics. The chemical treatment method mainly introduces reactive small-molecule inorganic or organic matter, or adsorptive polymer compounds into wooden cultural relics, and then dehydrates them after strengthening the mechanical properties of decayed wooden cultural relics. These methods combine the reinforcement and dehydration of wooden cultural relics, which is safer for cultural relic protection. However, due to the porosity and strong water absorption of wood, the introduced reinforcement agent is not easy to diffuse. Strengthening the diffusion depth of the reinforcement agent and dehydrating to maintain the stable structure of the cultural relics are the key to the dehydration and shaping reinforcement of water-saturated wooden cultural relics.

[0004] At present, most of the research on the protection of water-saturated wooden cultural relics is about the development of new protective materials, and there is little research on how to promote the penetration of protective materials in wooden cultural relics. However, no matter what kind of protective material, it is difficult to effectively penetrate into the wood by continuously interacting with water-saturated wooden cultural relics in a natural state. The difficulty of protective materials to penetrate into water-saturated wood is a common problem. Water-saturated wood has a three-dimensional porous structure mainly composed of polyhydroxy compounds. The water in the wood is mainly composed of free water in the cell cavity and cell wall mesopores and bound water in the cell wall. Water easily forms a hydrogen bond network with hydroxyl compounds, which restricts the flow and diffusion of water, especially water in capillaries. Therefore, it is difficult for water in water-saturated wood to achieve natural flow and diffusion in three-dimensional porous wood. Therefore, there is a lack of space in the water-saturated wood. Even if there is a concentration difference of protective materials inside and outside the wood, it is difficult for the protective materials to replace the water inside the wood through natural diffusion. They can only replace the water on the shallow surface of the wood to achieve the protection of the shallow surface of the wood. Summary of the invention

[0005] In view of the above technical problems in the prior art, the present invention provides a method for dehydrating and shaping water-saturated wooden cultural relics, which can solve the technical problem that the methods in the prior art are difficult to dehydrate and shape water-saturated wooden cultural relics.

[0006] The present invention provides a method for dehydrating and shaping water-saturated wooden cultural relics, comprising the following steps:

[0007] 1) a step of preparing a protective material solution or suspension, wherein the protective material is selected from any one of sucrose, sucralose, trehalose, polyethylene glycol, cellulose nanocrystals, and chitosan oligosaccharides, and the sucrose, sucralose, trehalose, polyethylene glycol, and chitosan oligosaccharides are prepared into an aqueous solution, wherein the solvent in the aqueous solution is water, or a mixture of water and ethanol; and the concentration in the aqueous solution is 5-60wt%;

[0008] The cellulose nanocrystals are prepared into a suspension, wherein the concentration of the suspension is 0.05-10wt%;

[0009] 2) Drying the water-saturated wooden cultural relics in a constant temperature and humidity environment for 0.5 to 1.5 hours; the temperature in the constant temperature and humidity environment is 20-25° C. and the humidity is 50-90%;

[0010] 3) applying the protective material solution or suspension to the water-saturated wooden cultural relic for 0.1 to 0.2 hours, and then drying for 0.5 to 1.5 hours;

[0011] 4) Repeat step (3) multiple times until the mass of the water-saturated wooden cultural relic remains unchanged after soaking;

[0012] 5) Dry the sample for 1.5 to 3 hours, and apply the protective material solution or suspension to the saturated wooden cultural relic for 0.2 to 0.4 hours.

[0013] 6) Repeat step (5) multiple times until the mass of the water-saturated wooden cultural relic remains unchanged after immersion;

[0014] 7) Drying the sample for 3 to 5 hours, applying the protective material solution or suspension to the saturated wooden cultural relic for 1.2 to 1.4 hours;

[0015] 8) Repeat step (7) multiple times until the mass of the water-saturated wooden cultural relic remains unchanged after immersion;

[0016] 9) Drying the treated saturated wooden cultural relics in a constant temperature and humidity environment for 1.5 to 2.5 hours, wherein the temperature in the constant temperature and humidity environment is 20-25° C. and the humidity is 50-90%; then transferring to room temperature and drying to constant weight.

[0017] Furthermore, the concentration of the protection material solution is 10-30wt%.

[0018] Furthermore, the concentration of the protective material suspension is 0.1-5wt%.

[0019] Furthermore, the protective material is applied to the water-saturated wooden cultural relic by at least one of a soaking method, a dripping method, and a spraying method.

[0020] Furthermore, the temperature in the constant temperature and humidity environment is 25° C., and the humidity is 80-90%.

[0021] Furthermore, as the number of repetitions increases, the dehydration time of the present invention varies within 0.5-6 hours, and the time for applying the protective material varies within 5-100 minutes. When the weight gain of the protective material remains unchanged, the dehydration time and the time for applying the protective material are increased to perform a new cycle. When the weight gain of the protective material no longer changes after increasing the dehydration time and the time for applying the protective material, the protected sample is dried to constant weight at constant temperature and humidity, room temperature, or first at constant temperature and humidity and then at room temperature.

[0022] Compared with the prior art, the present invention has the following characteristics:

[0023] 1) The present invention provides a method for dehydrating and shaping water-saturated wooden cultural relics step by step. First, the reinforcement material is diffused and adsorbed in the shallow structure of the wood to achieve local support reinforcement, and then the reinforcement area is dehydrated in a controlled manner to avoid excessive dehydration causing structural collapse in the unreinforced area. The dehydration of the reinforced area enhances the penetration of subsequent reinforcement agents.

[0024] 2) The method provided by the present invention for dehydrating and shaping water-saturated wooden cultural relics step by step is universal and can promote the penetration of various protective materials into water-saturated wooden cultural relics.

[0025] 3) The method provided by the present invention for dehydrating and shaping water-saturated wooden cultural relics step by step can not only promote the penetration of protective materials in water-saturated wood, but also promote the penetration of materials in other water-saturated porous three-dimensional structures.

[0026] Compared with the prior art, the technical effect of the present invention is positive and obvious. The present invention solves the problems of the existing water-saturated wooden cultural relic protection materials being difficult to penetrate and having a long protection period, and provides a method (CIM) for protecting water-saturated wooden cultural relics by rapid, effective, safe dehydration and cyclic immersion. Compared with the traditional immersion method (TSM), the method can effectively increase the penetration of the protection material and reduce the volume shrinkage of the protected wood. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a comparison diagram of the macroscopic morphology of the fresh sample after drying, the saturated wood sample with a water saturation rate of about 300%, and the protected samples of Examples 1-3 and Comparative Examples 1-3.

[0028] Figure 2 It is a comparison chart of the X-ray diffraction patterns of a fresh sample, a saturated wood sample with a water saturation rate of about 300%, Examples 1-3 and Comparative Examples 1-3.

[0029] Figure 3 It is a comparison chart of infrared spectra of a fresh sample, a saturated wood sample with a water saturation rate of about 300%, and samples of Examples 1-3.

[0030] Figure 4 It is a thermogravimetric comparison diagram of a fresh sample, a saturated wood sample with a water saturation rate of about 300%, and samples of Examples 1-3. DETAILED DESCRIPTION

[0031] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.

[0032] The present invention provides a method for dehydrating and shaping water-saturated wooden cultural relics step by step. Through the method provided by the present invention, the time required for protection is effectively shortened, the weight gain rate of the protection material of the sample after protection is significantly improved, and the volume shrinkage rate, one of the most important indicators for measuring the protection effect, is significantly reduced.

[0033] The following is an exemplary description of a method for dehydrating and shaping water-saturated wooden cultural relics provided by the present invention in stages, and the method may include the following steps.

[0034] In order to ensure the uniformity of the samples and the comparability of the protective effects, commercial tongue-pressing wood was selected as the simulated samples, which were uniformly soaked and heated in a strong alkaline solution for 2-10 hours, and then soaked in clean water until the pH was neutral.

[0035] In the protection of cultural relics, in order to prevent the actual cultural relics from being destroyed, the protective materials are usually first applied to simulated samples. In order to demonstrate the effectiveness of the method of the present invention, tongue-pressing wood with moderate decay and a saturation rate of about 300% was selected.

[0036] In some embodiments, the protective material can be selected from sucrose, sucralose, trehalose, polyethylene glycol, cellulose nanocrystals (CNCs), chitosan oligosaccharides; preferably, widely used protective materials and natural bio-based protective materials are selected.

[0037] Polyethylene glycol is a water-saturated wooden cultural relic protection material widely used in the world. Polyethylene glycol has been used to protect the Swedish Vasa shipwreck, the Chinese Huaguang Reef I shipwreck, etc.

[0038] Bio-based materials are not only highly compatible with wood but also biodegradable, and are widely used to protect water-saturated wooden artifacts, such as cellulose, chitosan oligosaccharides, etc. To further verify the effectiveness of the protection method, soluble and granular dispersible protection materials (suspensions) were selected.

[0039] In some embodiments, the concentration of the soluble protective material solution is 5-60wt%; preferably, the concentration of the soluble protective material solution is 10-20wt%; more preferably, the concentration of the soluble protective material solution is 15wt%. Too high a concentration of the soluble protective material may cause excessive osmotic pressure inside the wood, causing cell wall collapse and deformation of the wooden cultural relics; too low a concentration may prevent the protective material from effectively penetrating into the wood, resulting in a protective layer that is not deep enough and cannot provide adequate protection.

[0040] In some embodiments, the concentration of the granular dispersible protective material (suspension) is 0.05-10wt%; preferably, the concentration of the granular dispersible protective material (suspension) is 0.1-5wt%; more preferably, the concentration of the granular dispersible protective material (suspension) is 0.25wt%. If the concentration of the granular dispersible protective material is too high, not only may the osmotic pressure inside the wood be too high, causing the cell wall to collapse and the wooden cultural relics to deform, but it may also cause the protective material to be blocked on the surface of the cultural relics, affecting penetration; if the concentration is too low, the protective material may not be able to effectively penetrate into the wood, resulting in the protective layer not being deep enough and unable to provide adequate protection.

[0041] In the method for dehydrating and shaping water-saturated wooden cultural relics provided by the present invention, the dehydration temperature is 20-25°C and the humidity is 50-90%; preferably, the temperature is 25°C and the humidity is 80-90%. Since water-saturated wooden cultural relics are porous, saturated with water, soft and fragile, once exposed to the air, the surface tension generated by the evaporation of water easily causes the fragile cell wall to collapse, causing irreversible shrinkage and deformation of the entire wood. Therefore, the water-saturated wooden cultural relics should be dried slowly in a high humidity environment to avoid damage caused by excessive dehydration of the cultural relics.

[0042] In a method for dehydrating and shaping water-saturated wooden cultural relics provided by the present invention, the dehydration time varies within 0.5-6 hours, and the time for applying protective materials varies within 5-100 minutes. As the protection process proceeds, the protective material gradually enters the interior of the sample from the inside to the outside. The more protective materials enter the interior of the sample, the smaller the space inside the sample, the longer the entry path of subsequent materials, and the longer the time required. Therefore, as the protection process proceeds, the time for applying materials needs to be adjusted. The dehydration of the sample is a process from the outside to the inside. The more protective materials enter the sample, the longer the path for water volatilization, and the moisture content of the sample decreases. Therefore, as the protection process proceeds, the dehydration time needs to be adjusted.

[0043] In the method for dehydrating and shaping saturated wooden cultural relics provided by the present invention, the dehydration time and the time for applying the protective material are increased, and when the weight gain of the protective material no longer changes, the protected sample is dried to a constant weight at a constant temperature and humidity, at room temperature, or at a constant temperature and humidity first and then at room temperature, to ensure that the drying of the sample does not cause deformation of the sample.

[0044] It should be noted that the volume, degree of decay, tree species, etc. of saturated wood samples vary, so the concentration of protective materials, sample dehydration time, and time of applying protective materials all need to be optimized according to the conditions of the samples.

[0045] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0046] Example 1

[0047] Experiment on the protective effect of polyethylene glycol on samples of water-saturated wooden cultural relics through step-by-step dehydration and shaping.

[0048] A PEG aqueous solution with a concentration of 15 wt % and a relative molecular mass of 4000 was prepared.

[0049] The birch wood was selected to prepare a water-saturated decayed wood sample with a water saturation rate of 300%.

[0050] First, the sample was dried at a constant temperature and humidity for 1 hour. After that, the protective material was applied for 10 minutes. Subsequently, the protected sample was dried again for 1 hour. This drying and soaking cycle was repeated until the mass of the sample remained unchanged after soaking; the drying time and soaking time were extended to 2 hours and 20 minutes respectively, until the mass of the sample remained unchanged after soaking for 20 minutes; the drying time and soaking time were extended to 4 hours and 60 minutes respectively, until the mass of the sample remained unchanged after soaking for 60 minutes.

[0051] The protected samples were first dried in a constant temperature and humidity environment for 2 h, and then transferred to room temperature and dried to constant weight.

[0052] After drying, the sample of Example 1 gained 102.00%, had a volume shrinkage of 5.78%, and a ΔE of 5.00. The characteristic peaks of X-ray diffraction and infrared spectrum of polyethylene glycol appeared in the sample protected by the cyclic immersion method, and polyethylene glycol affected the thermal decomposition properties of the sample protected by the cyclic immersion method.

[0053] Comparative Example 1

[0054] Experiment on the protective effect of samples of water-saturated wooden cultural relics by dehydration and shaping using polyethylene glycol immersion method.

[0055] A PEG aqueous solution with a concentration of 15 wt % and a relative molecular mass of 4000 was prepared.

[0056] The birch wood was selected to prepare a water-saturated decayed wood sample with a water saturation rate of 300%.

[0057] The sample was immersed in a 15 wt % PEG aqueous solution for the same time as the sample in Case 1.

[0058] The protected samples were first dried in a constant temperature and humidity environment for 2 h, and then transferred to room temperature and dried to constant weight.

[0059] After drying, the sample of Example 1 gained 48.00% in weight, had a volume shrinkage of 22.89%, and a ΔE of 3.65. The characteristic X-ray diffraction peak of polyethylene glycol did not appear in the sample protected by the traditional immersion method.

[0060] Example 2

[0061] Experiment on the protective effect of chitosan oligosaccharide on samples of water-saturated wooden cultural relics by dehydration and shaping step by step.

[0062] A chitosan oligosaccharide aqueous solution with a concentration of 15wt% and a relative molecular mass of 3000 was prepared.

[0063] The birch wood was selected to prepare a water-saturated decayed wood sample with a water saturation rate of 300%.

[0064] First, the sample was dried at a constant temperature and humidity for 1 hour. After that, the protective material was applied for 10 minutes. Subsequently, the protected sample was dried again for 1 hour. This drying and soaking cycle was repeated until the mass of the sample remained unchanged after soaking; the drying time and soaking time were extended to 2 hours and 20 minutes respectively, until the mass of the sample remained unchanged after soaking for 20 minutes; the drying time and soaking time were extended to 4 hours and 60 minutes respectively, until the mass of the sample remained unchanged after soaking for 60 minutes.

[0065] The protected samples were first dried in a constant temperature and humidity environment for 2 h, and then transferred to room temperature and dried to constant weight.

[0066] After drying, the sample of Example 1 gained 81.00%, had a volume shrinkage of 19.04%, and a delta E of 25.58. The characteristic peaks of X-ray diffraction and infrared spectrum of chitosan oligosaccharide appeared in the sample protected by the cyclic immersion method, and chitosan oligosaccharide affected the thermal decomposition properties of the sample protected by the cyclic immersion method.

[0067] Comparative Example 2

[0068] Experiment on the protective effect of samples of water-saturated wooden cultural relics by dehydration and shaping using the chitosan oligosaccharide immersion method.

[0069] A chitosan oligosaccharide aqueous solution with a concentration of 15wt% and a relative molecular mass of 3000 was prepared.

[0070] The birch wood was selected to prepare a water-saturated decayed wood sample with a water saturation rate of 300%.

[0071] The sample was immersed in a 15 wt % chitosan oligosaccharide aqueous solution for the same time as the sample in Case 2.

[0072] The protected samples were first dried in a constant temperature and humidity environment for 2 h, and then transferred to room temperature and dried to constant weight.

[0073] After drying, the sample of Example 1 gained 50.00% in weight, had a volume shrinkage of 27.23%, and a ΔE of 18.59. The characteristic X-ray diffraction peaks of chitosan oligosaccharide did not appear in the sample protected by the traditional immersion method.

[0074] Example 3

[0075] Experiment on the protective effect of cellulose nanocrystals on samples of water-saturated wooden cultural relics by step-by-step dehydration and shaping.

[0076] A cellulose nanocrystal aqueous dispersion (suspension) with a concentration of 0.25 wt % was prepared.

[0077] The birch wood was selected to prepare a water-saturated decayed wood sample with a water saturation rate of 300%.

[0078] First, the sample was dried at a constant temperature and humidity for 1 hour. After that, the protective material was applied for 10 minutes. Subsequently, the protected sample was dried again for 1 hour. This drying and soaking cycle was repeated until the mass of the sample remained unchanged after soaking; the drying time and soaking time were extended to 2 hours and 20 minutes respectively, until the mass of the sample remained unchanged after soaking for 20 minutes; the drying time and soaking time were extended to 4 hours and 60 minutes respectively, until the mass of the sample remained unchanged after soaking for 60 minutes.

[0079] The protected samples were first dried in a constant temperature and humidity environment for 2 h, and then transferred to room temperature and dried to constant weight.

[0080] After drying, the sample of Example 3 gained 32.00%, had a volume shrinkage of 28.12%, and a ΔE of 7.18. The characteristic peaks of X-ray diffraction and infrared spectrum of cellulose nanocrystals appeared in the sample protected by the cyclic immersion method, and the cellulose nanocrystals affected the thermal decomposition properties of the sample protected by the cyclic immersion method.

[0081] Comparative Example 3

[0082] Experiment on the protective effect of samples of cellulose nanocrystal soaking method on dehydration and shaping of water-saturated wooden cultural relics.

[0083] A cellulose nanocrystal aqueous dispersion (suspension) with a concentration of 0.25 wt % was prepared.

[0084] The birch wood was selected to prepare a water-saturated decayed wood sample with a water saturation rate of 300%.

[0085] The sample was immersed in a 0.25 wt % aqueous dispersion of cellulose nanocrystals for the same time as the sample in Case 3.

[0086] The protected samples were first dried in a constant temperature and humidity environment for 2 h, and then transferred to room temperature and dried to constant weight.

[0087] After drying, the sample of Comparative Example 3 gained 10.00% in weight, had a volume shrinkage of 31.33%, and a ΔE of 1.13. The characteristic peak of X-ray diffraction of cellulose nanocrystals did not appear in the sample protected by the traditional immersion method.

[0088] Table 1 shows the weight gain, volume shrinkage and color difference of the saturated wood samples with a water saturation rate of about 300%, Examples 1-3 and Comparative Examples 1-3 compared to the fresh samples.

[0089] Table 1

[0090]

Claims

1. A method for dehydrating and shaping water-saturated wooden cultural relics, characterized in that The steps include: 1) a step of preparing a protective material solution or suspension, wherein the protective material is selected from any one of sucrose, sucralose, trehalose, polyethylene glycol, cellulose nanocrystals, and chitosan oligosaccharides, and the sucrose, sucralose, trehalose, polyethylene glycol, and chitosan oligosaccharides are prepared into an aqueous solution, wherein the solvent in the aqueous solution is water, or a mixture of water and ethanol; and the concentration in the aqueous solution is 5-60wt%; The cellulose nanocrystals are prepared into a suspension, wherein the concentration of the suspension is 0.05-10wt%; 2) Drying the water-saturated wooden cultural relics in a constant temperature and humidity environment for 0.5 to 1.5 hours; the temperature in the constant temperature and humidity environment is 20-25° C. and the humidity is 50-90%; 3) applying the protective material solution or suspension to the water-saturated wooden cultural relic for 0.1 to 0.2 hours, and then drying for 0.5 to 1.5 hours; 4) Repeat step (3) multiple times until the mass of the water-saturated wooden cultural relic remains unchanged after soaking; 5) Dry the sample for 1.5 to 3 hours, and apply the protective material solution or suspension to the saturated wooden cultural relic for 0.2 to 0.4 hours. 6) Repeat step (5) multiple times until the mass of the water-saturated wooden cultural relic remains unchanged after immersion; 7) Drying the sample for 3 to 5 hours, applying the protective material solution or suspension to the saturated wooden cultural relic for 1.2 to 1.4 hours; 8) Repeat step (7) multiple times until the mass of the water-saturated wooden cultural relic remains unchanged after immersion; 9) Drying the treated saturated wooden cultural relics in a constant temperature and humidity environment for 1.5 to 2.5 hours, wherein the temperature in the constant temperature and humidity environment is 20-25° C. and the humidity is 50-90%; then transferring to room temperature and drying to constant weight.

2. The method for dehydrating and shaping water-saturated wooden cultural relics according to claim 1, characterized in that: The concentration of the protective material solution is 10-30 wt %.

3. The method for dehydrating and shaping water-saturated wooden cultural relics according to claim 1, characterized in that: The concentration of the suspension is 0.1-5wt%.

4. The method for dehydrating and shaping water-saturated wooden cultural relics according to claim 1, characterized in that: The protective material is applied to the water-saturated wooden cultural relic by at least one of a soaking method, a dripping method, and a spraying method.

5. The method for dehydrating and shaping water-saturated wooden cultural relics according to claim 1, characterized in that: The temperature in the constant temperature and humidity environment is 25° C., and the humidity is 80-90%.

Citation Information

Patent Citations

  • Water-logged wooden cultural relic composite reinforcing material and preparation method thereof

    CN108393984A

  • Application of supercritical CO2 technology in desalinating and dewatering of marine archaeological wood

    CN110126042A

  • Efficient dehydration protection method for water-saturated wooden cultural relics

    CN117962050A

  • Shaping protection method for saturated archaeological wood

    CN118181434A